Tinea Corporis Caused by Trichophy-ton Benhamiae Transmitted by a Dog: First Case Report in Portugal - Tavares, E (2021)
Dermatophytoses are superficial and contagious infections caused by dermatophyte fungi. They are the most fre-quent infectious dermatosis in clinical practice, and can affect the skin, hair and nails. Its correct diagnosis allows the understanding of clinical, ecological and epidemiological aspects associated with these microorganisms. Clinical presentation is variable and depends on the habitat (human, animal or soil origin), virulence of the fungus and on the host’s immune status.We report the clinical case of a 62-year-old man with tinea corporis, which stands out for its exuberant clinical pres-entation and by the isolated agent, Trichophyton benhamiae (formerly known as Arthroderma benhamiae), an etiologi-cal agent of dermatophytosis that has not been scientifically reported in Portugal yet.